Implementation of Government Policy in Arranging Green Open Space in the City of Semarang - Al Giffari, Ilham (Yayasan Sinergi Kawula Muda, 2023)
Green Open Space (RTH) is an urban element that is very important to support all activities and life of the population. Basically, green open space is a natural element that plays an important role in creating a city that is proportional and environmentally friendly. According to the provisions in force, the proportion of green open space in urban areas is at least 30%. This step was taken by the government to ensure the balance of urban development. This study aims to describe the implementation of management policies and constraints in the arrangement of green open spaces in the city of Semarang experienced by the Spatial Planning Office and the Settlement and Housing Area Office of Semarang City. The approach used in writing this law is empirical juridical. In using the empirical juridical method, two approaches are used, namely the interview approach and field observations. In general, this interview approach uses trusted sources related to the problem being studied. Whereas in the direct observation approach the researcher goes directly to the field in researching the problems that are happening. Based on research results obtained in 2021 the area of public and private green open space is 1,042 ha and 4,025 ha private (15% of the city area) and in 2022 the area of public and private green open space is 2,580.585 (20.07% of the city area) ). It then explains the role of the Semarang City Government through the Spatial Planning Office and the Housing and Settlement Area Office in carrying out the implementation of the green open space arrangement policy. Next, the obstacles and solutions faced by the Semarang City Government will be explained in carrying out urban green open space planning.